Does a Progressive Wealth Tax Reduce Top Wealth Inequality? Evidence from Switzerland - Samira Marti; Isabel Martínez; Florian Scheuer (Center for Economic Studies and ifo Institute (CESifo), 2023)
Like in many other countries, wealth inequality has increased in Switzerland over the last fifty years. By providing new evidence on cantonal top wealth shares for each of the 26 cantons since 1969, we show that the overall trend masks striking differences across cantons, both in levels and trends. Combining this with variation in cantonal wealth taxes, we then estimate an event study model to identify the dynamic effects of reforms to top wealth tax rates on the subsequent evolution of wealth concentration. Our results imply that a reduction in the top marginal wealth tax rate by 0.1 percentage points in-creases the top 1% (0.1%) wealth share by 0.9 (1.2) percentage points five years after the reform. This suggests that wealth tax cuts over the last 50 years explain roughly 18% (25%) of the increase in wealth concentration among the top 1% (0.1%).
Keywords: H23; H24; D31; 330; wealth tax; inequality; top wealth shares